Mercadé-Fernández : Llull-Taulat, manzana 2, bloque PB+6 (2002)
Proyecto de renovación urbana en Barcelona con motivo del <Fórum>
Keywords: MERCADÉ-FERNÁNDEZ; BARCELONA; ESPAÑA; MERCADÉ, RICARD; FERNANDEZ, FRANC; PROYECTOS; VIVIENDAS MULTIFAMILIARES